The Impact of Precocious Puberty on Oral Health and Craniofacial Development in Children: A Scoping Review - Sari, Nadya Novia; Indriyanti, Ratna (Syntax Corporation Indonesia, 2025)
Precocious puberty is defined as the appearance of developmental characteristics of secondary puberty before the age of 8 years in girls and before the age of 9 years in boys. Hormonal changes related with this condition can influence oral health and craniofacial growth, not only general physical development. Children experiencing precocious puberty may have advanced dental age, expedited skeletal maturation, malocclusion, temporomandibular disorders (TMD), and alterations in oral microbiota. This study aims to identify the current evidence on the structural and functional impacts of precocious puberty on oral health and craniofacial development in children. This scoping review followed the Preferred Reporting Items for Systematic Reviews and Meta-analysis extension for Scoping Reviews (PRISMA-ScR) guidelines. A systematic literature search was retrieved using PubMed and EBSCOhost, includes publications from 2015 to 2025. The search focused on oral and craniofacial changes in children with precocious puberty, using specific keywords and the Population, Concepts and Context framework. Total of nine studies conducted from 2015 to 2025 on oral and craniofacial characteristics in children with precocious puberty. The studies used various designs, including cross-sectional, case-control, observational, and systematic review. Main topics included dental development, craniofacial growth, TMD, maloclusion, and oral microbiota changes. Most of the research involved children with precocious puberty and performed in several countries, and majority was in South Korea. Children with precocious puberty have substantial anatomical and functional changes in the oral and craniofacial complex. Dental and craniofacial changes occur earlier and progress more rapidly, necessitating timely diagnosis and interdisciplinary management. Awareness of these manifestations is essential for pediatric dentists, orthodontists, and endocrinologists to ensure optimal treatment planning during the critical growth period.